A RE-READING OF THE IDEA OF PROGRESS FROM THE ETHIC OF DISCOURSE (Andamios, Revista de Investigación Social, 2008)
This paper considers the criticisms made of the modern idea of progress which provoked negative consequences in history while it was equated with instrumental reason. This situation permitted those critics of reason to declare “the end of history”. However, this paper aims to review the former considering the ethics of discourse as a conceptual framework, as in Apel and Habermas, who aimed to address and revalue the emancipatory potential of reason and hold a perspective of sense for history.
Keywords: Sense of history; progress; communicative rationality; emancipation